Effect of a marine protected area on tropical estuarine fish assemblages: Comparison between protected and unprotected sites in Senegal. (November 2015) - Sadio, Oumar; Simier, Monique; Ecoutin, Jean-Marc; Raffray, Jean; Laë, Raymond; Tito de Morais, Luis
Abstract: A comparative study of fish assemblages of a marine protected area and an exploited area was carried out in the Sine Saloum estuary (Senegal, West Africa). Data were collected at these two sites between 2008 and 2011. The two areas are morphologically similar, and comparison of the physicochemical parameters (salinity, transparency, temperature and percentage of saturation of dissolved oxygen) showed that the water masses are similar. The bio-ecological indicators and ecological, trophic and size structures were also compared. Given the environmental similarity of the two sites, their differences in bio-ecological characteristics and fish assemblage organization can be explained by the protection status of the MPA. The species richness and fish abundance per sampling unit were higher in the exploited site, but the mean trophic level and the observed maximum size of individuals were higher in the MPA. Although slightly higher for the MPA, the differences observed for biomass and average size between the two sites were not significant. The beta diversity in the MPA was higher than in the exploited site. The fish assemblage was dominated in terms of abundance by two pelagic herbivores Ethmalosa fimbriata (80%) and Sardinella maderensis (12.3%) and in terms of biomass by E. fimbriata (37.4%) and a benthic predator, Arius latiscutatus (23.7%). The assemblage of the MPA had a marine affinity characterized by the presence of piscivorous or generalist predators; large individuals were not uncommon. In the exploited site, the fish assemblage was relatively stable, dominated in abundance by E. fimbriata (33.4%) and S. maderensis (32.8%). In terms of biomass, a species of mullet, Liza dumerili, ranked first (26.2%), followed by E. fimbriata (22.4%) and S. maderensis (14.9%). The assemblage in the exploited site had a more estuarine affinity, dominated by detritivorous or phytophagous herbivores. Individuals observed there were mostly of small or medium size. This study confirms that the establishment of MPA is an effective tool for restoring marine biodiversity and trophic structure of fish assemblages. Highlights: Fish assemblages of an MPA and an exploited site were compared in a tropical estuary. Total richness, mean trophic level and maximum length were higher in the MPA. The fish assemblage of the MPA had a marine affinity, with large predators. MPA are an effective tool for restoring biodiversity and trophic structure.